Three new species of flightless Cryptorhynchinae from the Caucasus (Coleoptera: Curculionidae) - Stüben, Peter E.; Japarashvili, Shota; Dallakyan, Marine; Astrin, Jonas J. (Zootaxa, 2025)
Three new weevil species, Kyklioacalles ocellus Stüben & Astrin, sp. nov., Onyxacalles gibbosus Stüben & Astrin, sp. nov., and Echinodera borjomiensis Stüben & Astrin, sp. nov. are described from the Caucasus (Georgia, Armenia, and Russia) and are distinguished from related species based on morphological and molecular data. The new taxa are included in a phylogram and a CO1 distance matrix is given including the closest species from the Caucasus and the eastern mediterranean region. Acalles reitteri Meyer, 1896 is transferred to the genus Kyklioacalles as Kyklioacalles reitteri (Meyer, 1896) comb. n. based on both morphological and molecular evidence.